Triptolide: reflections on two decades of research and prospects for the future. Issue 4 (4th November 2020) - Tong, Lu; Zhao, Qunfei; Datan, Emmanuel; Lin, Guo-Qiang; Minn, Il; Pomper, Martin G.; Yu, Biao; Romo, Daniel; He, Qing-Li; Liu, Jun O.
Abstract : This review highlights advances in material sourcing, molecular mechanisms, clinical progress and new drug design strategies for triptolide from a Chinese medicinal herb, along with some prospects for the future course of development of triptolide. Abstract : Covering: 2000 to 2020 Triptolide is a bioactive diterpene triepoxide isolated from Tripterygium wilfordii Hook F, a traditional Chinese medicinal plant whose extracts have been used as anti-inflammatory and immunosuppressive remedies for centuries. Although triptolide and its analogs exhibit potent bioactivities against various cancers, and inflammatory and autoimmune diseases, none of them has been approved to be used in the clinic. This review highlights advances in material sourcing, molecular mechanisms, clinical progress and new drug design strategies for triptolide over the past two decades, along with some prospects for the future course of development of triptolide.